Student Opinion of Instruction: System Interface Redesign Document - Faculty Senate, Valdosta State University; Downey, Steve (Valdosta, GA: Valdosta State University, 2016)
The SOI Redesign Document is a technical report that reviews the practices and research associated with gathering and reporting end of course student feedback (i.e., course evaluations). This document examines key issues affecting VSU current (2016) SOI system and its ability to accurately gather information necessary to improve the instructional effectiveness of faculty teaching courses as part of the Valdosta State University system. New interfaces and data collection strategies are presented in the report in order to update the current SOI system. The revisions proposed in this report were reviewed for a 60 period and then was voted upon and adopted by the VSU Faculty Senate on January 28, 2016.
1 electronic document. Faculty Senate report, January 28, 2016. 23 pages.
Keywords: Faculty Senate (Valdosta State University); Committees; Reports